DETERMINAN STRUKTUR MODAL BADAN USAHA MILIK NEGARA DI INDONESIA - mizan ahmad zarkasih; Mohammad adam; reza ghasarma (JEMBATAN, 2017)
The objectives of this research are to examine the effect of Firm Size, Growth Opportunity, Business Risk and Investment Opportunity Set influence simultaneously and partially on Capital Structure.Research conducted at the State-Owned Enterprises that listed on the Bursa Efek Indonesia period 2011-2015. The research population was 20 companies, with the sample of 17 companies with sampling using purposive sampling technique. The analytical method used is the factor analysis method and multiple linear regression analysis, which perviously tested with the classical assumption. The results showed that the Firms Size, Growth Opportunity, Business Risk, and the Investment Opportunity Set influence simultaneous on the Capital Structure.The research also revealed that, Firm Size influence positive significant, Growth Opportunity and Business Risk has no significant effect on Capital Structure, and Investment Opportunity Set influence negative significant on the Capital Structure. On the other hand, R-Square value amnounted at 57,6%, it’s mean that 57,6% movement of Capital Structure can be predicted from the movement of the four independent variables. Keyword : Capital Structure, Business Risk, Investment Opportunity Set